2019
DOI: 10.4103/jcd.jcd_387_18
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of passive ultrasonic irrigation, continuous ultrasonic irrigation versus irrigation with reciprocating activation device in penetration into main and simulated lateral canals

Abstract: Context: The use of chemicals solutions and means of activation is of utmost importance in endodontic treatment. Aims: This study compared three activation techniques used in the final irrigation of the endodontic treatment. Subjects and Methods: Eighty uniradicular teeth were instrumented with the Protaper Universal system up to F4 file. After decalcification, the teeth had artificial lateral canals created at 2, 4.5 and 6 mm from working le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…The passive ultrasonic continuous and intermittent irrigation methods were compared and evaluated by various researchers. [ 2 11 14 15 ] This study confirmed with the earlier found results and found continuous irrigation to be a more efficient method than the intermittent method of passive ultrasonic irrigation. However, the effect of time was insignificant in the present study which was in accordance with certain studies[ 2 11 ] but varied from other studies.…”
Section: Discussionsupporting
confidence: 86%
“…The passive ultrasonic continuous and intermittent irrigation methods were compared and evaluated by various researchers. [ 2 11 14 15 ] This study confirmed with the earlier found results and found continuous irrigation to be a more efficient method than the intermittent method of passive ultrasonic irrigation. However, the effect of time was insignificant in the present study which was in accordance with certain studies[ 2 11 ] but varied from other studies.…”
Section: Discussionsupporting
confidence: 86%